Project Energise: Using participatory approaches and real time computer prompts to reduce occupational sitting and increase work time physical activity in office workers - Gilson, N.; Ng, N.; Pavey, T.; Ryde, G.; Straker, Leon; Brown, W. (Elsevier, 2015)
© 2016 Sports Medicine Australia. Objectives: This efficacy study assessed the added impact real time computer prompts had on a participatory approach to reduce occupational sedentary exposure and increase physical activity. Design: Quasi-experimental. Methods: 57 Australian office workers (mean [SD]; age=47 [11] years; BMI=28 [5]kg/m2; 46 men) generated a menu of 20 occupational 'sit less and move more' strategies through participatory workshops, and were then tasked with implementing strategies for five months (July-November 2014). During implementation, a sub-sample of workers (n =24) used a chair sensor/software package (Sitting Pad) that gave real time prompts to interrupt desk sitting. Baseline and intervention sedentary behaviour and physical activity (GENEActiv accelerometer; mean work time percentages), and minutes spent sitting at desks (Sitting Pad; mean total time and longest bout) were compared between non-prompt and prompt workers using a two-way ANOVA. Results: Workers spent close to three quarters of their work time sedentary, mostly sitting at desks (mean [SD]; total desk sitting time = 371 [71]. min/day; longest bout spent desk sitting = 104 [43]. min/day). Intervention effects were four times greater in workers who used real time computer prompts (8% decrease in work time sedentary behaviour and increase in light intensity physical activity; p <. 0.01). Respective mean differences between baseline and intervention total time spent sitting at desks, and the longest bout spent desk sitting, were 23 and 32. min/day lower in prompt than in non-prompt workers (p <. 0.01). Conclusions: In this sample of office workers, real time computer prompts facilitated the impact of a participatory approach on reductions in occupational sedentary exposure, and increases in physical activity.